PENYULUHAN KEGIATAN RW 06 REWWIN: RUMAH PINTAR TUNAS BANGSA - Iin Rachmawati (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2019)
This counseling activity is based on the background of the situation that there is still a lack of knowledge of teachers and parents about the concepts and knowledge of smart parenting. Therefore, counseling is carried out for seven months with the main goal so that the concept of smart parenting to produce a smart and resilient future generation can be planned from an early age. This counseling uses observation and training methods for Tunas Bangsa teachers and parents. The result of this activity counseling in the RW 06 Rewwin environment was an increase in teachers' and parents' understanding of what smart parenting is. In addition, the Tunas Bangsa students also began to become more open to their parents. For example, many students already have intense communication with their parents when delivering or when picking up has never been done before. So, it can be seen that there are very significant results both in relation to the development of teachers’and parents' understanding of smart parenting and also in direct relation to the students.